Social networking sites and learning in international relations: The impact of platforms - Pallas, Josh; Eidenfalk, Joakim; Engel, Susan (Australasian Journal of Educational Technology, 2019)
This article reports on a pilot undergraduate subject that incorporated a range of technology-enhanced learning approaches including online lectures, an online site for in and out of class communications, and strong encouragement for students to blog and use Twitter. This paper evaluates student engagement through the social networking sites (SNS), focusing on the online communication and content platform. We examine whether changing from an educationally oriented SNS platform to Facebook impacted on student engagement and feedback. To achieve this, both empirical data and qualitative student feedback were used.